Heterogeneous transmission mechanism: monetary policy and financial fragility in the euro area - Matteo Ciccarelli; Angela Maddaloni; José-Luis Peydró (European Central Bank (ECB), 2013)
The Euro area economic activity and banking sector have shown substantial fragility over the last years with remarkable country heterogeneity. Using detailed data on lending conditions and standards, we analyse how financial fragility has affected the transmission mechanism of the single Euro area monetary policy during the crisis until the end of 2011. The analysis shows that the monetary transmission mechanism has been time-varying and influenced by the financial fragility of the sovereigns, banks, firms and households. The impact of monetary policy on aggregate output is stronger during the financial crisis, especially in countries facing increased sovereign financial distress. This amplification mechanism, moreover, operates mainly through the credit channel, both the bank lending and the non-financial borrower balance-sheet channel. Our results suggest that the bank-lending channel has been partly mitigated by the ECB nonstandard monetary policy interventions. At the same time, when looking at the transmission through banks of different sizes, it seems that, until the end of 2011, the impact of credit frictions of borrowers have not been significantly reduced, especially in distressed countries. Since small banks tend to lend primarily to SME, we infer that the policies adopted until the end of 2011 might have fall short of reducing credit availability problems stemming from deteriorated firm net worth and risk conditions, especially for small firms in countries under stress.
Keywords: E44; E52; E58; G01; G21; G28; 330; credit channel; financial crisis; heterogeneity; monetary policy; non-standard measures